Integration of Mechatronic Functions on Additively Manufactured Components via Laser‐Assisted Selective Metal Deposition - Vieten, Tobias; Weser, Sascha; Schilling, Alexander; Gläser, Kerstin; Zimmermann, André (Advanced functional materials, 2024)
The current industrial revolution derives much of its momentum from value creation based on interconnected products and related data based services. Such products must fulfill both mechanical and electrical requirements, making them mechatronic systems. The production of such systems via additive manufacturing (AM) processes offers advantages in achievable complexity, reduction of the amount of individual components, and cost‐effective as well as sustaina ble production of small quantities. In this work, a process chain is presented that allows for refining additively manufactured 3D structures made from industry‐standard materials into mechatronic components by creating electrically conductive structures directly on their surfaces. The process chain is based on masking the component's surface and selectively removing the masking according to the circuit geometry using laser radiation. In a wet–chemical bath process, the surface is then exposed to palladium nuclei, the masking is fully removed and metal layers (copper/nickel/gold) are deposited by electroless plating. The procedure is developed using stereolithography as a model process for AM and transferred to four additional AM methods. In all cases, despite markedly different surface properties, good selectivity of metal deposition is observed as well as adhesion strength and conductivity comparable to industrially common injection‐molded laser direct structured mechatronic interconnect devices. The production of small to medium quantities of mechatronic interconnect devices via additive manufacturing offers advantages such as cost and time effectiveness, increased sustainability and higher complexity. Without using specialized materials, the presented SANCHO method allows for an electronic function integration on components produced by an arbitrary additive manufacturing technology via laser structuring and chemical plating.